Pengaruh Locus Of Control, Financial Knowledge dan Parental Income terhadap Perilaku Pengelolaan Keuangan (Studi pada Mahasiswa Baru Program Studi Manajemen Tahun 2021 Universitas Muhammadiyah Gresik) - Wasti Reviandani (JMK (Jurnal Manajemen dan Kewirausahaan), 2022)
The rapid development of this rapid technology can have a negative impact such as unlimited human needs, causing people to be unable to manage personal finances properly and trigger financial conditions to become less stable. This phenomenon can lead to consumptive financial behavior in the community, especially students, meaning that the community lacks awareness of financial behavior. This study uses a quantitative approach that aims to determine whether locus of control, financial knowledge and parental income can influence the financial management behavior of new students of the management study program, University Muhammadiyah Gresik. The use of purposive sampling technique in sampling obtained 152 correspondents who were then analyzed use multiple linear regression analysis technique with SPSS 16 program. The result is Locus of control has a significant positive effect, Financial Knowledge has a significant positive effect, and Parental Income has an insignificant negative effect on management behavior finance for New Students Management Study Program, Universitas Muhammadiyah Gresik in 2021.